Activity and safety of nivolumab, an anti-PD-1 immune checkpoint inhibitor, for patients with advanced, refractory squamous non-small-cell lung cancer (CheckMate 063): a phase 2, single-arm trial. Issue 3 (March 2015) - Rizvi, Naiyer A; Mazières, Julien; Planchard, David; Stinchcombe, Thomas E; Dy, Grace K; Antonia, Scott J; Horn, Leora; Lena, Hervé; Minenza, Elisa; Mennecier, Bertrand; Otterson, Gregory A; Campos, Luis T; et al.
Summary: Background: Patients with squamous non-small-cell lung cancer that is refractory to multiple treatments have poor outcomes. We assessed the activity of nivolumab, a fully human IgG4 PD-1 immune checkpoint inhibitor antibody, for patients with advanced, refractory, squamous non-small-cell lung cancer. Methods: We did this phase 2, single-arm trial at 27 sites (academic, hospital, and private cancer centres) in France, Germany, Italy, and USA. Patients who had received two or more previous treatments received intravenous nivolumab (3 mg/kg) every 2 weeks until progression or unacceptable toxic effects. The primary endpoint was the proportion of patients with a confirmed objective response as assessed by an independent radiology review committee. We included all treated patients in the analyses. This study is registered withClinicalTrials.gov, numberNCT01721759 . Findings: Between Nov 16, 2012, and July 22, 2013, we enrolled and treated 117 patients. 17 (14·5%, 95% CI 8·7–22·2) of 117 patients had an objective response as assessed by an independent radiology review committee. Median time to response was 3·3 months (IQR 2·2–4·8), and median duration of response was not reached (95% CI 8·31–not applicable); 13 (77%) of 17 of responses were ongoing at the time of analysis. 30 (26%) of 117 patients had stable disease (median duration 6·0 months, 95% CI 4·7–10·9). 20 (17%) of 117 patients reported grade 3–4 treatment-related adverse events, including: fatigue (five [4%] of 117 patients), pneumonitis (four [3%]), and diarrhoea (three [3%]). There were two treatment-associated deaths caused by pneumonia and ischaemic stroke that occurred in patients with multiple comorbidities in the setting of progressive disease. Interpretation: Nivolumab has clinically meaningful activity and a manageable safety profile in previously treated patients with advanced, refractory, squamous non-small cell lung cancer. These data support the assessment of nivolumab in randomised, controlled, phase 3 studies of first-line and second-line treatment. Funding: Bristol-Myers Squibb.